PWE-099 Faecal Calprotectin: Help or Hinderance in Evaluating Patients with Lower GI Symptoms. (4th June 2013) - Allison, M; Hu, M; Puritz, S; Richards, T; El-Farhan, N
Abstract : Introduction: Several studies demonstrate the potential of faecal calprotectin measurement in distinguishing inflammatory bowel disease (IBD) from irritable bowel syndrome (IBS). It is unclear, however, to what extent such measurements alter patient investigation and management over standard history taking, examination and routine blood tests. Methods: We reviewed all faecal calprotectin results from samples submitted by adults not previously known to have IBD between February 2010 and April 2012. Using the health board's Clinical Workstation relevant outpatient letters, results of subsequent investigations and clinical outcomes were reviewed. A calprotectin value of > 60ug/g was considered elevated. Results: Cinical data was missing for 13 of the 266 patients. Of 155 with a normal result management was unaltered in 126, of whom 50 were referred for lower GI endoscopy before their result was known. In another 5 patients IBD was later found despite a normal result. A normal result may have obviated the need for colonoscopy or capsule endoscopy in 17, and otherwise altered management in 12 other patients. Outcomes for the 98 with an elevated result are summarised in the table. Patient management was unaltered in 60. There were 33 for whom an elevated result prompted colonoscopy and/or capsule endoscopy, and results were normal in 27. Five others still await colonoscopy or capsule. Conclusion: This study casts doubt on the value of faecal calprotectin in the routine evaluation of patients presenting with lower GI symptoms. Invasive investigations prompted by elevated results proved normal much more often than abnormal. The assay seems most helpful in evaluating patients with symptoms suggestive of IBS with abnormal blood tests, and in those in whom previous investigations were equivocal for IBD Disclosure of Interest: None Declared.